Stimulating the Picohydropower Market for Low-Income Households in Ecuador - Green, John (World Bank, Washington, DC, 2014)
The main aim of this World Bank-ESMAP project has been to pave the way for picohydro to become accessible to low-income households in Ecuador, with the view to replicating the process in the Andean region and other developing countries. This has been done through five main activities: (1) assessing the main experiences in picohydro technology and market developments, looking particularly at Vietnam and the Philippines1; (2) reviewing the existing use of microhydro in five Andean countries2 and assessing their potential picohydro market; (3) establishing 31 pilot picohydro projects in two provinces of Ecuador with full participation of the end users in local communities; (4) encouraging a sustainable local infrastructure for supporting picohydro technology in Ecuador through training local technicians and bringing local dealers forward to consider picohydro as a business venture; and (5) conducting a rapid rural appraisal in the communities before and after the installation of the picohydro pilots to consider the technological and social impacts in the Ecuadoran situation.